2013
DOI: 10.1186/2008-2231-21-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of exopolysaccharide with immunomodulatory activity from fermentation broth of Morchella conica

Abstract: Background and the purpose of this studyMushroom polysaccharides have traditionally been used for the prevention and treatment of a multitude of disorders like infectious illnesses, cancers and various autoimmune diseases. In vitro and in vivo studies suggest that certain polysaccharides affect immune system function. Morchella conica (M. conica) is a species of rare edible mushroom whose multiple medicinal functions have been proven. Thus, the objective of this study is to isolate and characterize of exopolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 22 publications
(28 reference statements)
0
29
2
Order By: Relevance
“…4d, the monosaccharides contents of EPS-2 were Rha (94.39 %) and Gal (5.61 %) with the molar ratio of 44.5:2.9. Some reports showed that the monosaccharide composition of EPS of M. conica (Su et al 2013), Pycnoporus sanguineus (Cao et al 2014) and B. aereus was Man, Glu, Glu, respectively, which were differ from our results of the EPS by F. velutipes SF-06. According to the above results, the monosaccharide composition of EPS was also different from that of EPS-1 or EPS-2.…”
Section: Monosaccharides Compositioncontrasting
confidence: 84%
See 1 more Smart Citation
“…4d, the monosaccharides contents of EPS-2 were Rha (94.39 %) and Gal (5.61 %) with the molar ratio of 44.5:2.9. Some reports showed that the monosaccharide composition of EPS of M. conica (Su et al 2013), Pycnoporus sanguineus (Cao et al 2014) and B. aereus was Man, Glu, Glu, respectively, which were differ from our results of the EPS by F. velutipes SF-06. According to the above results, the monosaccharide composition of EPS was also different from that of EPS-1 or EPS-2.…”
Section: Monosaccharides Compositioncontrasting
confidence: 84%
“…3 FT-IR spectra of EPS-1 and EPS-2 at the range of 400-4,000 cm -1 C=O asymmetric stretching vibration absorption peak and the peaks at 1,618.19 and 1,457.17 cm -1 indicated the presence of -NH 2 and -COOH groups in EPS-2 (Cerna et al 2003). According to the results stated above, the EPS by F. velutipes SF-06 is novel in its structure, compared to the reports on Morchella conica of EPS (Su et al 2013) and Boletus aereus ).…”
Section: Uv and Ft-ir Spectra Of Eps-1 And Eps-2mentioning
confidence: 61%
“…Activating macrophages and cytokines [147,148] Grifolan Grifola frondosa Activating macrophages and lymphokines [149] Lentinan Lentinus edodes T-cell-oriented adjuvant [149] PS-G Ganoderma lucidum Activating macrophages and T lymphocytes [135,136] Schizophyllan Schizophyllum commune Activating T cell, increasing interleukin and TNF-α production [150] Terpenoids…”
Section: Morchella Esculenta Morchella Conicamentioning
confidence: 99%
“…An appropriate protocol for the isolation, quantification and characterization of EPS is essential so that each step of the process, fermentation medium, isolation purpose and characterization method is carefully adjusted for each type of previously planned EPS. 14,15…”
Section: Technological Processing For Eps Obtentionmentioning
confidence: 99%